Repatriation of the Persecuted Rohingya Through an ICJ Verdict: Utopia or an Equitable Remedy? - Md. Rizwanul Islam; Naimul Muquim (Washington University Global Studies Law Review, 2025)
The mass exodus of the persecuted Rohingya has attracted the attention of the international community, and many countries around the world have condemned the atrocities perpetrated by Myanmar. This paper examines a judgment of the International Court of Justice (“ICJ” or “the Court”) and explores why and how the safe and dignified repatriation of the Rohingya to their homeland in Myanmar, would be a feasible solution to ameliorate the mistreatment of the Rohingya. By examining jurisprudence of the ICJ and relevant international legal provisions, the article demonstrates that this remedy could play a significant role in rendering justice that goes beyond mere symbolism.
Keywords: International Court of Justice; Repatriation; Rohingya; Myanmar